Expressing the building energy systems thermodynamic seasonal efficiency - Januševičius, Karolis; Bielskus, Juozas; Martinaitis, Vytautas; Streckienė, Giedrė; Rimdžius, Dovydas (International Conference “Environmental Engineering”, 2017)
In order to reduce impact to environment, a qualitative approach of energy saving is global aspect that is included in various forms of CO2 emissions, primary energy limitations and benchmarks in EU and member countries policy. Exergy analysis allows expressing the quality of energy flows in comparison to ambient or other reference conditions. Despite of this valuable information, this concept is not widely used in engineering practice. The article suggests the calculation procedure for sessional or periodical thermodynamic (exergy) efficiency in relation to variable reference conditions. Knowledge about defined procedures unlocks the possibility to fill up the implementation gap for building system engineering practice where seasonal performance parameters are widely used to express efficiency. Prepared algorithm allows determining seasonal or periodic thermodynamic efficiency of individual elements and energy transfer chains in building energy systems. Defined calculation procedure workflow is suitable for integrated approach when coupled heat transfer and fluid flow processes are explored in short time steps with dynamic simulation software tools. Presented algorithm ensures result that fits in thermodynamically correct range 0-1 and helps to summarize separate time step results. By adding duration of specific conditions, this analysis enables to identify critical peak periods and base load conditions across operation period. The presented framework fills the gap in lack of systematic expression for seasonal thermodynamic efficiency and suggests the process for calculation procedures workflow.